Heavy metal tolerance and antibiotic resistance of actinomycetes isolated from tin tailings and forest soil / Hema Thopla Govender - Hema Thopla , Govender (2014)
A collection of 421 actinomycetes, isolated from an ex-tin mining area in Bidor (238 isolates) and soil samples collected from Pasoh forest (183 isolates), was successfully revived from FRIM Actinobacteria Culture Collection. Rapid metal tolerance screening procedures that involved the use of solid synthetic media containing Cd2+, Cu2+, Hg2+, Ni2+, Pb2+, Zn2+ and As3+ allowed the selection of 29 metal tolerant isolates. The selected isolates were further assayed for antibiotic resistance. Pearson Correlation analysis showed that a positive correlation (r = 0.359) exist between multiple antibiotic resistance and heavy metal tolerance in the actinomycetes isolated from Bidor while no correlation was observed among the Pasoh isolates (r = - 0.192). Further, all 29 isolates were assayed for metal toxicity in liquid minimal media (MM). Based on the metal toxicity assay, 13 potential metal tolerant isolates were selected. Eight of these isolates were able to tolerate at least one metal ion at the highest test concentration while three isolates able to tolerate Ni2+ at the second highest concentration and another two isolates showed moderate tolerance to Cu2+ and Hg2+, respectively. All the isolates were de-replicated based on their DNA fingerprint using BOX-PCR. Out of these isolates, TY049-057 from Bidor and TY028-047 from Pasoh were analysed for their ability to uptake Cd2+ into the cell biomass. Isolates TY028-047 and TY049-057 were identified as Streptomyces lannensis (100% similarity) and Streptomyces malaysiensis (100% similarity), respectively, based on 16S rRNA gene sequence analysis. Both isolates showed maximum Cd2+ uptake at day 8 when grown in liquid MM media containing an initial concentration of 1mM Cd2+. The maximum uptake of Cd2+ in isolate S. lannensis was 4.66 umol Cd2+/mg dry cell mass while 3.17 umol Cd2+/mg dry cell mass was recorded in isolate S. malaysiensis. The findings from this study showed that maximum Cd2+ uptake was observed in both tolerant isolates during the stationary phase of growth profile. A significant increase in Cd2+ uptake after 8 days of growth were observed in S. lannensis from Pasoh and not in S. malaysiensis from Bidor. This may be explained by the metal tolerance screening and metal toxicity assay results where strains isolated from Pasoh showed higher ability to tolerate Cd2+ compared to Bidor. Further, many other aspects influence the level of Cd2+ uptake such as nutrients, metal concentration in the media and growth viability rate of bacteria. The two Cd2+ tolerant isolates represent potential candidates to be used as agents in bioremediation of Cd2+ containing wastewaters and soil.